Evidence for four- and three-wave interactions in solar type III radio emissions - G. Thejappa; R. J. MacDowall; M. Bergamo (Annales Geophysicae, 2013)
The high time resolution observations obtained by the STEREO/WAVES experiment show that in the source regions of solar type III radio bursts, Langmuir waves often occur as intense localized wave packets with short durations of only few ms. One of these wave packets shows that it is a three-dimensional field structure with WLneTe ~ 10−3, where WL is the peak energy density, and ne and Te are the electron density and temperature, respectively. For this wave packet, the conditions of the oscillating two-stream instability (OTSI) and supersonic collapse are satisfied within the error range of determination of main parameters. The density cavity, observed during this wave packet indicates that its depth, width and temporal coincidence are consistent with those of a caviton, generated by the ponderomotive force of the collapsing wave packet. The spectrum of each of the parallel and perpendicular components of the wave packet contains a primary peak at fpe, two secondary peaks at fpe ± fS and a low-frequency enhancement below fS, which, as indicated by the frequency and wave number resonance conditions, and the fast Fourier transform (FFT)-based tricoherence spectral peak at (fpe, fpe, fpe + fS, fpe − fS), are coupled to each other by the OTSI type of four-wave interaction (fpe is the local electron plasma frequency and fS is the frequency of ion sound waves). In addition to the primary peak at fpe, each of these spectra also contains a peak at 2fpe, which as indicated by the frequency and wave number resonance conditions, and the wavelet-based bicoherence spectral peak at (fpe, fpe), appears to correspond to the second harmonic electromagnetic waves generated as a result of coalescence of oppositely propagating sidebands excited by the OTSI. Thus, these observations for the first time provide combined evidence that (1) the OTSI and related strong turbulence processes play a significant role in the stabilization of the electron beam, (2) the coalescence of the oppositely propagating up- and down-shifted daughter Langmuir waves excited by the OTSI probably is the emission mechanism of the second harmonic radiation, and (3) the Langmuir collapse follows the route of OTSI in some of the type III radio bursts.